(untitled) (Bangladesh Journal of Urology, 2020)
Testicular neoplasm and infertility are two common complications of cryptorchidism. Early surgical treatment of undescended testis i.e. between 3 to 12 months of age appears to lower the risk of complications. If done later, the risk of testicular cancer cannot be eliminated. Another important thing is that for diagnosing testicular neoplasm open biopsy or core biopsy is usually not done before operation. If essential, it is done through inguinal route during surgery (frozen section biopsy), and is never through scrotal route until and otherwise it has already invaded the scrotal skin causing ulceration. In that case there may be chance of spreading malignancy into inguinal lymph nodes. Bangladesh Journal of Urology, Vol. 20, No. 1, January 2017 p.49-51